2015
DOI: 10.1002/jsfa.7078
|View full text |Cite
|
Sign up to set email alerts
|

Petroselinum crispum has antioxidant properties, protects against DNA damage and inhibits proliferation and migration of cancer cells

Abstract: BACKGROUND Petroselinum crispum (English parsley) is a common herb of the Apiaceae family that is cultivated throughout the world and is widely used as a seasoning condiment. Studies have shown its potential as a medicinal herb. In this study, P. crispum leaf and stem extracts were evaluated for their antioxidant properties, protection against DNA damage in normal 3T3‐L1 cells, and the inhibition of proliferation and migration of the MCF‐7 cells.RESULTSThe dichloromethane extract of P. crispum exhibited the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…In another study, ethanolic leaves extracts show higher polyphenolic and flavonoid contents (54.2 and 42.1 mg/g, re spectively) than methanolic and chloroform extracts. The two major phenolic compounds extracted from parsley are apiin and malonyl apiin; flavonoids are the major compounds in this plant; apigenin, cosmosiin, oxypeucedanin hydrate are detected in the aqueous extracts of the leaves; the main flavonol constituents found are kaempferol and quercetin (Farzaei et al, 2013;Tang et al, 2015;Trifunschi and Ardelean, 2012).…”
Section: Phenolics Flavonoids and Antioxidant Propertiesmentioning
confidence: 99%
“…In another study, ethanolic leaves extracts show higher polyphenolic and flavonoid contents (54.2 and 42.1 mg/g, re spectively) than methanolic and chloroform extracts. The two major phenolic compounds extracted from parsley are apiin and malonyl apiin; flavonoids are the major compounds in this plant; apigenin, cosmosiin, oxypeucedanin hydrate are detected in the aqueous extracts of the leaves; the main flavonol constituents found are kaempferol and quercetin (Farzaei et al, 2013;Tang et al, 2015;Trifunschi and Ardelean, 2012).…”
Section: Phenolics Flavonoids and Antioxidant Propertiesmentioning
confidence: 99%
“…In contrast, sardines with 2% chives showed the highest level of COPs (235.9 μg/g), which was the lowest protective effect (16.6%) among the percentages and herbs tested in this work. The phenolic compounds present in parsley and chives have been shown to act as natural antioxidants in different research by different authors (Jia and others ; Parvu and others ; Pereira and Tavano ; Tang and others ; Sęczyk and others ).…”
Section: Resultsmentioning
confidence: 99%
“…They have also attracted attention as they can prevent lipid oxidation in fish and fish products (Sancho and others ; Maqsood and others ; Frank and others ; Maqsood and others ; Figueirêdo and others ; Meleiro and others ; Tarvainen and others ; Vaisali and others ). Aromatic herbs are used worldwide by various culinary cultures and the antioxidant effects of parsley ( Petroselinum crispum ) and chives ( Allium schoenoprasum L.) have been evaluated and proven (Zhang and others ; Jia and others ; Sęczyk and others ; Tang and others ; Sęczyk and others ). The aromatic herbs, parsley, and chives are good sources of essential nutrients such as vitamins and minerals as well as antioxidant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic constituents are flavonol glycosides of quercetin, apiol, myristicin and luteolin. phthalides, Terpenes, furanocoumarins apiin, carotenoids, ascorbic acid, and tocopherol are also present in P. crispum 6 .…”
mentioning
confidence: 99%
“…It also plays the role of carminative stomachic, abortifacient, and nutritive agent. Numerous Studies have shown that P. crispum has hypoglycemic, diuretic, hypolipidemic, antimicrobial, and anticoagulant and hepatoprotective properties 6 .…”
mentioning
confidence: 99%